Ultrasonographic & biochemical analysis of thyroid bio-architecture for further pharmacological intervention in adult Arabian stallions & mares. (February 2023) - El-Sherif, M.A.; Nabil, Ghazal; Ibrahim, Rana; Mohamed, Nourhan; Mohamed, Mona; Jaheen, Alaa Helal
Abstract: Based on the growing attention to the Arabian horses with a lack of records regarding their normal physiological parameters, which are critically vital for disease diagnosis &convenient drug administration, we give great attention to their thyroid gland normalcy. The thyroid gland is one of the key players in regulating many physiological processes. Therefore, we tackled thyroid biology & morphology in 14 Arabian stallions & 18 Arabian mares from the beginning of March to the middle of April on animals from 4 to 19 years old. First, the blood samples taken from their jugular vein were used for hematological profile, lipid profile, glucose-coagulation axis & thyroid profile. Moreover, thyroid gland dimensions & volume were estimated using ultrasonography. Noteworthy, Arabian mares have significantly higher MCH & relative eosinophils than Arabian stallions, while Arabian stallions have significantly higher glucose levels than Arabian Mares. Interestingly, this study found that Arabian horses have a high level of Total T4 & low level of platelets count compared to other horses. These results pointed to the deiodinase inhibitors as a possible target therapy for hyperthyroidism & thyroid cancer in Arabian horses, making surgery a second option. Also, these results refer to the caution required before giving Arabian horses high plasma protein bounded drugs, especially anticoagulants. Also, sonographic results showed that the left lobe is larger than the right lobe in both genders, & the lobes volume is larger in Arabian horses compared to others. These results would guide the veterinarian during diagnosis & thyroidectomy. Graphical abstract: Unlabelled Image Highlights: Determine the hematological parameters in both stallions & mares. Serum biochemical analysis, including the lipid profile & glucose-coagulation axis. Determine the normal values of thyroid profile in both stallions & mares using equids specific kits. Estimate the normal dimensions & volumes of the right & left thyroid lobes in both stallions & mares by ultrasonography. Meanwhile, the difference between genders was evaluated using a statistical t-test. Moreover, the measured parameters in Arabian horses were compared to the normal parameters of other horses using kits reference values & published papers. This research unveil many question marks regarding their endurance, performance, heat tolerance, & low vulnerability to cardiovascular diseases.